E-Learning and Social Media, Application in the Case of Logistics Training: An Analysis of Professional Use - Chavigné Jorba, Victor; Ruiz-Viñales, Carmen; Gómez Llauger, Nuria (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2026)
This research examines the use of social media in e-learning training for logistics professionals. The results show that social media is highly valued for its ability to build professional networks, facilitate access to educational content, and contribute to the development of digital skills. Among the most prominent platforms are WhatsApp, LinkedIn, and YouTube, due to their effectiveness in communication. Participants view the use of these tools—employed in their professional sphere—as a positive support in academic contexts, helping to improve communication and learning in e-learning environments. This study offers an innovative perspective, as training in the field of logistics has been scarcely explored, highlighting the importance of researching and leveraging these tools in a sector crucial to the global economy.